Improving Learning Performance in Physical Education through Video-Based Presentations (VBP) Approach - Culajara, Carla Jobelle (Physical Education and Sports: Studies and Research, 2023)
Background: Technology plays a pivotal role in the learning and teaching process. Technology has become a powerful tool for enhancing students' performance in Physical Education. The study aims to assess the effect of video-based presentations on students' physical education learning performance. Objectives: The study aims to assess the effects of video-based presentations as an intervention tool in enhancing students' performance. Specifically, this is to answer the following objectives: (1) mean scores in the pre-test and post-test, (2) significant difference between before and after intervention, and (3) student's experiences in using video-based presentations in the learning performance in physical education. Methods: The researcher used a sequential mixed-method research design with a one-group pre-test and post-test design, which was participated by 52 students in one of the secondary schools in the Philippines and five students in the focus group discussion. Purposive sampling was used to choose the participants to assess the effect of the video-based presentations. JASP Software was used to analyze the data. Results: Based on the result, the study shows that before the intervention, students needed more knowledge and more participation in the discussion. However, utilizing the intervention indicates that the video-based presentation significantly affects students' learning performance, which shows that the video-based presentation has a positive impact on the students' learning performance. Moreover, two themes emerged in the focus group discussion: independent learning and flexible instruction. Conclusion: As education becomes man's equalizer, students must adopt 21st-century skills, and through the intervention used, this will pave the way for developing their capabilities and skills in the education trends. This implies that with the progressive world facing the ever-changing education landscape, teachers must have the desire to build their technological capabilities by upskilling and retooling their innovativeness and creativity in delivering instructions.